计算 -2x^6-(-3x^2)^3
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 10:09:40
计算-2x^6-(-3x^2)^3计算-2x^6-(-3x^2)^3计算-2x^6-(-3x^2)^3-2x^6-(-3x^2)^3=-2x^6-(-27x^6)=-2x^6+27x^6=25x^6=
计算 -2x^6-(-3x^2)^3
计算 -2x^6-(-3x^2)^3
计算 -2x^6-(-3x^2)^3
-2x^6-(-3x^2)^3
=-2x^6-(-27x^6)
=-2x^6+27x^6
=25x^6
=-12x+18x=6x 数字与数字相乘 再合并同类项(未知数前的系数相加)
x/x-3-5x/x^2-x-6计算
计算:x/x-2 - 5x/x²-x-6计算:x/x-3 - 5x/x²-x-6
计算:(x+1)(x-2)(x-3)(x-6)
计算:[(x^2 - 4)/(x^2 - x - 6) + (x+2)/(x-3)] / (x+1)/(x-3)
计算:(-x^4)^3-(x^2)^6
x(x-2)(2x-3)计算
计算: (x+3)(x²-x-2)
计算 (x+3)(x²-x-2)
2x*4x-3x计算
计算:(x+2)/(x^2 - x - 6) + 2x/(x^2 - 3x) - x/(x^2 - 6x + 9)
计算 2+x+3/x-1*x^2-2x+1/x^2+6x+9
x^2+x-6分之x^2+3x-x^2-4分之x+2计算
计算(x-2)(x-3)+2(x+6)(x-5)-3(x平方-7x+13)
计算x^2-5x+6/x^2-1/x^2+x/x-3
(x-6)(x的平方+x+1)-x(2x+1)(3x-1)计算
-3x+6x^2-3x^3怎么计算
计算:(3x+2)/5-(x-6)=x/3
计算(6x^2-4x)/(3x-2)